2020
DOI: 10.1109/access.2020.3026630
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Lightweight Key Agreement and Authentication Scheme for WBAN

Abstract: Wireless Body Area Network (WBAN) is a promising field that may improve the quality of life by using it in patients' health monitoring process. However, the mobility and open access of wireless networks have resulted in several security gaps which may lead to critical health-related data compromise issues. Therefore, there existed a need to develop a mechanism to secure patient health-related data from all security impairments. Recently, Kompara et al.[1] proposed a lightweight authentication scheme that depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 31 publications
0
41
0
1
Order By: Relevance
“… We have proved the correctness of our scheme by welladopted BAN logic and informally verified by using the Automated Validation of Internet Security Protocol and Applications (AVISPA) tool.  We have further tuned up the computational cost and energy consumption of the proposed work compared to our earlier work [10]. The performance analysis of our scheme showed that our scheme outperforms based on computational and energy consumption overheads and security characteristics.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“… We have proved the correctness of our scheme by welladopted BAN logic and informally verified by using the Automated Validation of Internet Security Protocol and Applications (AVISPA) tool.  We have further tuned up the computational cost and energy consumption of the proposed work compared to our earlier work [10]. The performance analysis of our scheme showed that our scheme outperforms based on computational and energy consumption overheads and security characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…However, the performance results showed that the scheme holds equivalent ground in terms of computation time, energy consumptions, computational cost, and storage overheads. Moreover, on scrutinizing further, we unleashed few vulnerabilities in Kompara et al [9] like sensor node impersonation, base-station, and Intermediate Node (IN) compromise attacks and offered solutions to these vulnerabilities in one of our earlier works, Rehman et al [10]. In the work of Rehman et al, we offered an enhanced scheme by providing not only the solution of identified vulnerabilities but also made architectural level vital changes in the original scheme.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For healthcare field, the major contributors of authentication schemes include: a light-weight authentication protocol for cloud-based health-care systems (LAPCHS) [34]; a two-factor authentication scheme for Wireless Body Area Network (WBAN) [35]; Secure and light-weight RFID authentication protocol for Medical IoT (SecLAP) [36]; a light-weight mutual authentication and key agreement protocol for remote surgery application in tactile internet environment [37], and authentication for e-healthcare using 5G [38]. Some other health-related approaches are also seen in [39]- [41].…”
Section: A Light-weight Authentication Protocolsmentioning
confidence: 99%
“…An efficient Lightweight Key Agreement and Authentication Scheme for WBAN is proposed in (69) . The scheme is an effort to overcome the security gaps particularly base station compromise attack and sensor node impersonation attack found in the method proposed by M. Kompara et al (70) .…”
Section: Traditional Key Agreement Schemesmentioning
confidence: 99%